ANALISIS KETERGANTUNGAN FISKAL PEMERINTAH DAERAH DI PROVINSI SULAWESI SELATAN PADA ERA OTONOMI DAERAH - Fattah, Sanusi; ., Irman (Prosiding Seminas, 2012)
ABSTRACT This study aims to determine the level of fiscal dependence of the South Sulawesi Provincial Government by measure the performance / financial capacity of local governments using the degree of Fiscal Decentralization readiness and local governments in financial management,Ã‚Â  if fully funded by local government revenue and the local revenue sharing funds. Data in the form of research reports Local Government Finance Statistics and the population of South Sulawesi province in 2001-2008. While the analysis method used was descriptive statistics. The results showed that the performance / financial capability of South Sulawesi Provincial Government is still low when measured by the degree of Fiscal Decentralization Indicator, as well as readiness of local government in the face of regional autonomy, especially in finance, as measured by how far the ability of affairs when the financing is fully funded by local government revenue and revenue sharing funds is still low. This illustrates the level of Government Fiscal dependence in this area is still high. Keywords: Autonomy, performance / capability of Finance, Regional Readiness, Fiscal dependency.